Pengaruh Mata Diklat Produktif Akuntansi, Kompetensi Siswa, dan Lingkungan Keluarga Terhadap Kesiapan Kerja Melalui Mediasi Efikasi Diri - Nurussyifa, Roesma; Listiadi, Agung (Universitas Pendidikan Ganesha, 2021)
This research was an associative quantitative research which aims to determine whether or not there was an influence of of accounting productive subject, student competence, family environment on work readiness either directly or through self-efficacy mediation in class XI accounting students of SMK Negeri 2 Buduran. The sample calculation used the simple random sampling method with the Slovin formula and obtained a sample of 86 students of class XI accounting at SMK Negeri 2 Buduran in the 2019/2020 school year. The technique of collecting data used interviews, documentation to obtain the value of accounting productive subject, and closed questionnaires that had been tested for validity and reliability. The data analysis technique used descriptive analysis, data transformation, and hypothesis testing of direct and indirect effects. The results of the direct effect test are the accounting productive subject, student competence, and self-efficacy affect work readiness. Meanwhile, the family environment has no effect on work readiness. The indirect effect test, namely self-efficacy, can mediate the effect of student competence and the family environment on work readiness. However, self-efficacy cannot mediate the effect of the accounting productive subject on work readiness.